Pengembangan Media Pembelajaran MUTA (Monopoli Ular Tangga) dalam Pembelajaran Matematika Materi Operasi Hitung Bilangan Bulat - Herlin Fajriah; M. Jaya Adi Putra; Syahrilfuddin (LP2M Universitas Adzkia, 2022)
This research is a development research to produce learning media in the form of MUTA (monopoly snake and ladder) game on integer arithmetic operations using the guessing method. The purpose of this development research is to develop a media game